2011
DOI: 10.1002/cncr.25988
|View full text |Cite
|
Sign up to set email alerts
|

Upfront observation versus radiation for adult pilocytic astrocytoma

Abstract: BACKGROUND: Although pilocytic astrocytoma accounts for up to 40% of all childhood brain tumors, it is a rare disease in adults. Consequently, there are few mature data on the impact of up-front treatment options after surgery that include observation or adjuvant radiotherapy. METHODS: Ten women and 20 men were identified who were diagnosed with pilocytic astrocytoma from 1971 to 2007 and were retrospectively reviewed. The median patient age was 30 years (range, 18-64 years), and the median follow-up was 87 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 90 publications
2
18
1
3
Order By: Relevance
“…Hence, in order to explore the genetic characteristics and associated signaling pathways as well as identify possible pharmacologic targets in APAs, this study was undertaken. All the 59 patients in the present study showed median age, age range, tumor site and MIB-LI nearly similar to the previous studies on adult PAs (14,18,33,40,44).…”
Section: Discussionsupporting
confidence: 89%
“…Hence, in order to explore the genetic characteristics and associated signaling pathways as well as identify possible pharmacologic targets in APAs, this study was undertaken. All the 59 patients in the present study showed median age, age range, tumor site and MIB-LI nearly similar to the previous studies on adult PAs (14,18,33,40,44).…”
Section: Discussionsupporting
confidence: 89%
“…9 Investigators from Princess Margaret Hospital identified 30 adult patients diagnosed from 1971 -2007 and noted 10-year progression-free survival and overall survival rates of 35% and 85%, respectively. 10 The improved outcome in this prospective trial compared with the two retrospective trials is likely due to the younger patient population enrolled in the prospective trial (with no patients over 47 years old) and the high rate of gross total resection. A review of adult pilocytic astrocytoma patients identified in the Surveillance, Epidemiology, and End Results (SEER) Program confirmed younger age and greater extent of resection to be positive prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…2 Other studies have shown that while adjuvant RT significantly improves tumor control it has no impact on survival (due to efficacy of salvage therapies). 10 In the current prospective trial, a treatment paradigm of resection followed by close observation, reserving RT for salvage or for biopsy-only patients, resulted in good patient function over time. Neurologic function, prospectively measured and quantified with the NFS, was stable or improved for the majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The present literature also supports up-front radiotherapy for pilocytic astrocytoma although mainly in adults. Ishkanian et al [5] published a study of adult pilocytic patients managed with up-front radiotherapy. They found that progression-free survival was superior in the radiation group than the observation group.…”
Section: Discussionmentioning
confidence: 99%